Fear of COVID-19, risk perception and preventive behavior in health workers: a cross-sectional analysis in middle-income Latin American countries - Bonilla-Asalde, César Antonio; Rivera-Lozada, Oriana; Ipanaqué-Zapata, Miguel; Castro-Alzate, Elvis Siprian; Pacheco-Lopez, Robinson; Rivera-lozada, Isabel Cristina; Chong, Félix; Sagastume, Lucrecia Ramírez (Frontiers in Public Health, 2023)
The aim of this study was to examine the association between fear of COVID-19 and risk perception with preventive behavior in health professionals from four Latin American countries. An analytical cross-sectional study was conducted. Health professionals with on-site care in Colombia, Ecuador, Guatemala, and Peru were surveyed. Information was collected through an online self-report questionnaire. The main variables were preventive behavior as the dependent variable and fear of COVID-19 and risk perception as independent variables. Linear regression was used, and unstandardized beta coefficient and value of ps were calculated. Four hundred and thirty-five health professionals were included, the majority were aged 42 years or older (45.29, 95%CI: 40.65–50.01) and female (67.82, 95%CI: 63.27–72.05). It was shown that the greater the fear of COVID-19, the greater the preventive behavior of COVID-19 infection (B = 2.21, p = 0.002 for total behavior; B = 1.12, p = 0.037 for additional protection at work; B = 1.11, p < 0.010 for hand washing). The risk perception of COVID-19 infection had a slight direct relationship with preventive behaviours (B = 0.28, p = 0.021 for total behavior; B = 0.13, p = 0.015 for hand washing), with the exception of the preventive behavior of using additional protection at work (p = 0.339). We found that fear and risk perception are associated with increased practice of hand washing and use of additional protection at work. Further studies are required on the influence of working conditions, job performance and the occurrence of mental health problems in frontline personnel with regard to COVID-19.